A novel tannase from Klebsiella pneumoniae KP715242 reduces haze and improves the quality of fruit juice and beverages through detannification - Kumar, Mukesh; Mehra, Ravinder; Yogi, Rajesh; Singh, Nitesh; Salar, Raj Kumar; Saxena, Gauri; Rustagi, Sarvesh (Frontiers in Sustainable Food Systems, 2023)
The presence of high tannin content in fruit juices and other beverages generates bitterness and haze formation with a concomitant deterioration of their quality. This problem could be circumvented by treating these food products with the enzyme tannase (tannin acyl hydrolase EC 3.1.1.20), which contains the ability to hydrolyze the ester and depside linkages present in hydrolyzable tannins. In the present study, a low molecular weight (38.20 kDa) tannase purified from Klebsiella pneumoniae KP715242 was used for clarification and detannification of orange juice, beer, and tea cream solubilization. The initial tannin content of orange juice was reduced to 42.45% upon treatment with 4.5 U/mL of purified tannase at 35°C for 3.5 h. Beer haze was clarified by incubating the colloidal suspension with the purified enzyme. Under the optimum condition of temperature (30°C), incubation time (3.5 h), and enzyme concentration (4.5 U/mL), the initial tannin content of beer was reduced to 46.47%. Tea cream solubilization was achieved by treating the tea extract with varying enzyme concentrations at different time intervals and temperatures. The maximum reduction in the tea tannin content (55%) was observed at 35°C when the enzyme was incubated for 3 h at a concentration of 6.0 U/mL. The results of this investigation could be further exploited at an industrial scale in the detannification of fruit juice, beer, and tea.